Taxing Capital in an Imperfectly Competitive Economy - Sheikh Selim (Cardiff University, Cardiff Business School, 2005)
Evidence of declining trend in OECD economies' income tax rates and the concern of enhancing competition in the US and the EU product markets subtly motivate the question if low income tax rates are optimal in an imperfectly competitive economy. This paper examines optimal income tax policy in a dynamic neoclassical model with monopoly distortions. A capital subsidy, motivated by low private returns to capital, provides strong incentive to invest, but the adverse welfare effect of investment is not perceived by capital owners. Since profit seeking investment worsens second best welfare, and this effect is only perceived by the government, there is a strong motivation to tax capital. The paper presents a numerical characterization of the Ramsey policy and shows that switching to a Ramsey policy involving a capital tax is welfare improving.
Keywords: D42; E62; H21; H30; 330; Optimal taxation; Monopoly power; Ramsey policy